Alternative Treatment Method of Diabetes Mellitus Patients with Vast and Lastingly Nonhealing Wounds - Militsa, N. N.; Soldusova, V. V. (Problems of Cryobiology and Cryomedicine, 2008)
The treatment of vast trophic ulcers and long-term nonhealing wounds at Diabetes mellitus is difficult because of wound process phase extension. The results of treatment for 15 patients getting a local treatment with current methods and 12 patients with application of cell-tissue therapy preparations were analyzed. The treatment result is the reduction of terms of wound debridement and acceleration of reparative process.